METHODS OF USING EDUCATIONAL AND SKILLS OF STUDENTS IN TRAINING - Saidov Ikhtiyor; Boltaboev Abdugani Mamirovich; Yusupov Arabboy Bukhodirjon; Mekhmonaliyev Shokhmukhammad (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, the interaction of human potential and computer tools are expressed on the basis of systematic, technological approaches of pedagogical technology.